In passage perilous : Malta and the convoy battles of June 1942 - O'Hara, Vincent P., 1951- (Twentieth-century battles, 2013)
By mid-1942 the Allies were losing the Mediterranean war: Malta was isolated and its civilian population faced starvation. In June 1942 the British Royal Navy made a stupendous effort to break the Axis stranglehold. The British dispatched armed convoys from Gibraltar and Egypt toward Malta. In a complex battle lasting more than a week, Italian and German forces defeated Operation Vigorous, the larger eastern effort, and ravaged the western convoy, Operation Harpoon, in a series of air, submarine, and surface attacks culminating in the Battle of Pantelleria. Just two of seventeen merchant sh.